Pharmacokinetics, Tissue Distribution, Metabolism and Excretion of a Novel COX-2 Inhibitor, Vitacoxib, in Rats - Wang, Jianzhong; Kong, Jingyuan; Yang, Yuxin; Liu, Yu; Qiu, Jicheng; Gong, Xiaohui; Zhang, Lu; Li, Jing; Sun, Feifei; Cao, Xingyuan (Frontiers in Veterinary Science, 2022)
The objectives of this study were to elucidate absorption, tissue distribution, excretion, and metabolism of vitacoxib, a novel selective cyclooxygenase-2 inhibitor, in Wistar rats. Vitacoxib was detected in most tissues within 15 min, suggesting that it was well distributed. Moreover, it could cross the intestinal barrier. Vitacoxib was mainly eliminated as two metabolites. Nine proposed metabolites of vitacoxib were found in the plasma, bile, urine, and feces of rats. Two main metabolites, 4-(4-chloro-1-(5-(methyl-sulfonyl) pyridin-2-yl)-1H-imidazol-5-yl) phenyl methanol (M1) and 4-(4-chloro-1-(5-(methyl-sulfonyl) pyridin-2-yl)-1H-imidazol-5-yl) benzoic acid (M2), were identified in rat feces and urine. Further, the authentic standards of M1 and M2 were synthesized to confirm their structures. The carboxylic acid derivative was the major metabolite of vitacoxib excreted in the urine and feces. Hydroxylation of the aromatic methyl group of vitacoxib and additional oxidation of the hydroxymethyl metabolite to a carboxylic acid metabolite were the proposed metabolic pathways. Vitacoxib displayed a high AUClast (4895.73 ± 604.34 ng·h/mL), long half-life (4.25 ± 0.30 h), slow absorption (Tmax, 5.00 ± 2.00 h) , and wide tissue distribution in rats. Our findings provide significant information for the further development and investigation of vitacoxib as an effective nonsteroidal anti-inflammatory agent, and highly its potential for use future in a clinical setting.